Cefepime-induced encephalopathy: socio-clinical patterns and electroencephalographic findings - Marques, Vitor Roberto Pugliesi; Marques, Lúcia Helena Neves; Araujo Filho, Gerardo Maria de; Abdalla, Nabila Darido; Galego, Andressa Regina; Fachini, Vitor Brumato; Muniz, Felipe Henrique; Medeiros, Breno Gonçalves (Arquivos de Neuro-Psiquiatria, 2025)
Cefepime is an antibiotic widely used for severe infections in hospital . However, its use can lead to encephalopathy, which is detected by electroencephalogram (EEG).To establish the socioclinical pattern of cefepime encephalopathy and its correlation with EEG.Forty-one medical records of patients diagnosed with cefepime-induced encephalopathy were analyzed according to the criteria established by Naranjo et al.,1 with socioclinical parameters being evaluated.All EEG tracings in the presence of cefepime-induced encephalopathy had generalized periodic discharges (GPD), and 70.7% of the exams met the criteria for a nonconvulsive status epilepticus. With the withdrawal of cefepime, 85.3% of patients had clinical improvement.Encephalopathy caused by cefepime is a clinical manifestation that should be considered among patients using this antibiotic, with a wide spectrum of manifestations. The use of EEG imaging is critical for diagnosis.
Keywords: Brain Diseases; Cefepime; Electroencephalography; Health Profile; Infections